Medieval Welsh History and the Revival of Celtic and Greek Mythology in T.A. Barron’s Merlin: The Lost Years (1996 - Arour, Faiza; Bentaher, Soumia (University ofAmmar Theledji -Laghouat, 2022)
Fantasy literature shares a lot of similar patterns and characteristics with ancient myths, these patterns are known as “archetypes”. The analysis of archetypes in literature is the subject of a modern literary theory called “mythological criticism”, a theory which has roots related to history, mythology, and even psychology. This theory focuses on the concept of “the collective unconscious” which appeared as a psychological explanation to humans universal imagination that has been leading them to recreate ancient mythical symbols and themes. Although both fantasy and myths share the same aspect of unreality, some authors did a great job combining these two elements with real ancient history and documented facts. The historification of myth in T.A. Barron’s Merlin The Lost Years (1996), is what this research will be dedicated to explore, along with the conscious and the unconscious recreation of myths through patterns, themes, and characters of this novel. From the title of Barron’s book, the reader already expects to see much of the ancient Celtic myth of Merlin, however, it is not the only thing he ends up finding there. Barron uses intertextuality and archetypes to refer to Greek/Celtic mythology, and also to Welsh medieval history. This dissertation, therefore, aims to discover the relation between history, myth, and fantasy literature, through the analysis of Merlin: The Lost Years (1996). This analysis will sort out the related elements to medieval Welsh history, the Celtic, and the Greek mythology, and will also examine the way collective unconscious manifests itself in the recreation of mythological patterns